Wordwall Interaction Media Development to Increase Mathematical Connection and Visual Thinking of Junior High School Students - Putra, Muhammad Allegra Prima Aristya; Baiduri, Baiduri; Zukhrufurrohmah, Zukhrufurrohmah (FKIP Universitas Lampung, 2024)
In today's digital era, optimizing the use of technology in education has become a primary focus for enhancing the quality of learning. One potential innovation in this area is the use of interactive media in the teaching and learning process, which not only increases students' interest but also deepens their understanding of concepts and mathematical skills. This study aims to develop an interactive learning media based on Wordwall that can improve mathematical connection abilities and visual thinking skills among junior high school students. This research is a development study (R&D) following the ADDIE research method, which begins with the analysis phase, followed by the design phase, the development phase, the implementation phase, and concludes with the evaluation phase. The study was conducted in the even semester of the 2023/2024 academic year, involving eighth-grade students as research subjects. The research instruments used include media validation sheets, student response questionnaires, and tests of mathematical connection abilities and visual thinking skills. The results indicate that the Wordwall-based learning media has very high validity, with a validation score of 95.2%. The tests of mathematical connection abilities and visual thinking skills show that this media can improve students' mathematical connection abilities at a moderate level, with an N-Gain value of 0.419, and enhance visual thinking skills at a low level, with an N-Gain value of 0.241. Additionally, this media was also rated as highly practical, with a practicality score of 88.8%. Overall, this Wordwall-based learning media is valid, effective, and practical, making it recommended for use in teaching to improve students' mathematical connection abilities and, to a lesser extent, their visual thinking skills. Keywords: interactive media, Wordwall, mathematical connections, visual thinking.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp569-581